PERANAN PSIKOLOGI KEPOLISIAN DALAM PROSES PENYIDIKAN (STUDI KASUS MUTILASI DI SIAK) - Ester Ailen Sirait; Erdiansyah '; Erdianto ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In Psychology police use mentioned in Law No. 2 of 2002 on the Indonesian National Police in Article 14 Paragraph 1 (h): Holding a police identification, police and forensic laboratory medicine and psychology of police for the benefit of police duties. Psychology of police as a branch of psychology is the application of the concepts of psychology to law enforcement agencies, meaning that the main concepts of psychology used for law enforcement in order to achieve justice, using the techniques of certain commonly applied psychology so that the investigator to conduct an examination of the suspect was not need to get angry and can steer the suspect in order to provide answers that are correct, regardless of the fact whether he is guilty or not, as well as in criminal psychology confronted the investigator as an examiner can confront the perpetrators of criminal acts better in order to expedite the course of the examination in the level of investigation. Given psychology backgrounds, behavior and alleged acts by approaching the psychological, which is expected to expedite the task penginterogasian / examination suspects without an attitude of coercion / emphasis be a problem in this research is how the role of psychology of police in the examination of a suspect in the case of mutilation in Siak, psychological barriers to the use of police force in the examination of a suspect in the case of mutilation in Siak. The purpose of this study is to determine the role of psychology in helping the police to conduct examination on suspected cases of mutilation in Siak, knowing any obstacles in the use of psychology of police and the efforts made to overcome the obstacles. The research method that the author has to do is research sosiologisdisamping it also juridical sociological approach that is done by looking at the correlation between the law society, so as to reveal the effectiveness of the rule of law in society. Through research the author has done, implementation of the psychological police are still going well in practice is due to the task of psychology police have difficulty in terms of the authority to conduct the examination without any request terlabih advance of the investigating authorities, which would restrict the movement of the psychology of the police to do more to do investigative efforts that need to be done by the police are: 1. Keep their willingness dati strategically positioned from the Police so that more police psychological role in the disclosure of the case at this stage of the investigation. 2. Increasing the educational programs for the police, especially for those who are at the front dibarisan (investigator). Thus the implementation of the psychological role of the police should be improved better with socialization in order to investigations conducted in accordance with Law No. 2 of 2002 on the Indonesian National Police Article 14, paragraph 1 (h) so that the rights of suspects are protected in accordance with applicable law.Key Words: Police Psychology - Mutilation – Investigation